Longitudinal ventricular cerebrospinal fluid profile in patients with spontaneous subarachnoid hemorrhage - Zinganell, Anne; Bsteh, Gabriel; Di Pauli, Franziska; Rass, Verena; Helbok, Raimund; Walde, Janette; Deisenhammer, Florian; Hegen, Harald (Frontiers in Neurology, 2022)
Background Spontaneous subarachnoid hemorrhage (SAH) is a severe neurological disease that frequently requires placement of external ventricular drainage (EVD). Cerebrospinal fluid (CSF) obtained via the drain is used to detect potential complications of SAH. Objective This study aimed to describe the longitudinal profile of routine CSF parameters in patients with SAH and to identify associations with neurological complications. Methods A total of thirty-three patients with spontaneous SAH who required an EVD and had at least three consecutive CSF samples collected over a period of more than 7 days were included in this study. Results A median of 6 longitudinally collected CSF samples per patient were available within 1–22 days after SAH onset. Overall, red blood cells (RBC) steadily decreased over time, whereas white blood cells (WBC) and total protein (TP) increased until days 6 and 13, respectively, and decreased thereafter. The estimated decay rates of RBC, WBC, and TP were 28, 22, and 6% per day. Distinct CSF patterns over time were linked to known complications after SAH. Patients with rebleeding showed increased RBC, TP, and phagocytosing cells compared to patients without re-bleeding. For ventriculitis, an elevated cell index with a higher proportion of granulocytes was characteristic. CSF of patients with delayed cerebral ischemia showed increased RBC and WBC compared to patients without DCI. Early CSF WBC and cell index were predictive for the occurrence of DCI and ventriculitis later during the disease course. The amount of daily CSF drainage via EVD had no impact on routine CSF parameters. Conclusion Longitudinal CSF characteristics are associated with SAH-related complications.